Sensitivity to eye gaze in autism: is it normal? Is it automatic? Is it social? - Nation, K; Penny, S (2008)
Children with autism are developmentally delayed in following the direction of another person's gaze in social situations. A number of studies have measured reflexive orienting to eye gaze cues using Posner-style laboratory tasks in children with autism. Some studies observe normal patterns of cueing, suggesting that children with autism are alert to the significance of the eyes, whereas other studies reveal an atypical pattern of cueing. We review this contradictive evidence to consider the extent to which sensitivity to gaze is normal, and ask whether apparently normal performance may be a consequence of atypical (nonsocial) mechanisms. Our review concludes by highlighting the importance of adopting a developmental perspective if we are to understand the reasons why people with autism process eye gaze information atypically.